A formação continuada para o uso das Tecnologias Digitais de Informação e Comunicação no processo de ensino e aprendizagem: uma análise com base no modelo TPACK - REIS, Maria Aparecida dos (2025)
This research is linked to the research line "Training and Action of Teaching Professionals and Educational Practices," of the Postgraduate Program in Education at the University of Western São Paulo (Unoeste). The study aimed to investigate the continuing training of Basic Education teachers in the state of Mato Grosso, provided by the Training and Updating Centers for Basic Education Professionals in the State of Mato Grosso (Cefapro), focusing on the knowledge inherent to the teaching profession, described in the TPACK model, for pedagogical practice mediated by Digital Information and Communication Technologies (DTIC). Regarding the methodological approach, the research tipology followed the assumptions of a case study, in a qualitative approach. The locus of the research was the 15 Cefapros, with the participants being public school teachers from Mato Grosso, directors, trainers, training coordinators from the Cefapros, and selected teachers who had developed successful practices in schools. The corpus consisted of document analysis, a questionnaire, and semi-structured interviews. The data analysis procedures included Discursive Textual Analysis (DTA) and data triangulation, aiming to combine different data collection methods to consolidate conclusions about the research object. We concluded that continuing education for the use of technologies has been essential for the advancement of education in the state of Mato Grosso but requires collective efforts to overcome the identified barriers and maximize the positive impacts of this training. We believe that the research provided important insights into the continuing teacher training teachers for the use of DITC offered by the Cefapros in the state of Mato Grosso, and can contribute to future training, especially by encouraging the approach to the knowledge described in the TPACK model.